Efficacy and safety of anti-CD38 monoclonal antibodies-based therapy versus standard therapy in newly diagnosed multiple myeloma patients: a systematic review and meta-analysis - Muhammad Osama; Muhammad Haris Khan; Safeena Khan; Amna Hussain; Ammara Tahir; Mehran Ullah; Abdullah Afridi; Ubaid Ullah; Wajeeh Ur Rehman (Therapeutic Advances in Hematology)
Background: Anti-CD38 monoclonal antibodies (mAbs) have significantly changed the multiple myeloma treatment landscape. This meta-analysis compared the efficacy and safety of anti-CD38 mAb-based therapy versus standard therapy in newly diagnosed multiple myeloma (NDMM) patients. Methods: We performed a comprehensive literature search on PubMed, the Cochrane Database, and ClinicalTrials.gov. The primary outcomes were progression-free survival (PFS) and minimal residual disease (MRD) status. Dichotomous outcomes were pooled using risk ratio (RR) along with the 95% confidence interval (CI) in RevMan 5.4. Subgroup analysis and meta-regression analysis were performed. The RoB 2.0 tool was used to assess the risk of bias. Results: Our meta-analysis included 11 randomized controlled trials. There were 5270 patients; 3040 TEs and 2230 TIEs. Anti-CD38 mAbs significantly improved MRD negativity (RR 1.94, 95% CI: 1.59–2.37; p < 0.00001) and PFS (RR 0.51, 95% CI: 0.45–0.58; p < 0.00001). Subgroup analyses revealed better outcomes for both the TE (MRD: RR 1.52, 95% CI: 1.37–1.68; PFS: RR 0.43, 95% CI: 0.34–0.54) and TIE (MRD: RR 3.49, 95% CI: 2.65–4.61; PFS: RR 0.55, 95% CI: 0.47–0.64) populations. Meta-regression revealed that Eastern Cooperative Oncology Group (ECOG) score 0 significantly influenced MRD status (β = −0.015, p < 0.05), whereas ECOG scores 1 and 2 lacked statistical significance. Subgroup analysis revealed that PFS was significantly different between standard (RR 0.47) and high (RR 0.81) cytogenetic risk groups. Conclusion: In NDMM patients, anti-CD38 mAb-based therapy significantly improved MRD status, and PFS compared with standard therapy alone, in both TE and TIE patients, suggesting a favorable benefit–risk profile.